TINDAK PIDANA KORUPSI DI BIDANG PERPAJAKAN - Saidi, Muhammad Djafar (Jurnal Hukum dan Peradilan, 2013)
Implementation of the tax law in casu UUKUP aims to educate taxpayers fulfill their rights and duties, but tax officials and tax officials to enrich themselves abused in the form of committing corruption in the field of taxation. Since the rule of law because of the tremendous UUKUP authorizes the tax authorities that tax officials to make it happen. Therefore, the rule of law in UUKUP require realignment to prevent corruption in the field of taxation. Keywords: Crime, Corruption, Taxation